The price of thirst : global water inequality and the coming chaos - Piper, Karen Lynnea, 1965- (University of Minnesota Press, 2014)
"There's Money in Thirst," reads a headline in the New York Times. The CEO of Nestlé, purveyor of bottled water, heartily agrees. It is important to give water a market value, he says in a promotional video, so "we're all aware that it has a price." But for those who have no access to clean water, a fifth of the world's population, the price is thirst. This is the frightening landscape that Karen Piper conducts us through in The Price of Thirst--one where thirst is political, drought is a business opportunity, and more and more of our most necessary natural resource is controlled by multinational corporations. The product of seven years of investigation across six continents and a dozen countries, and scores of interviews with CEOs, activists, environmentalists, and climate change specialists, The Price of Thirst paints a harrowing picture of a world out of balance, with the distance between the haves and have-nots of water inexorably widening and the coming crisis moving ever closer.